Alcohol dependence and stigmatization - Yılmaz, Mualla; Cüceler, Seval (Journal of Dependence, 2019)
Stigmatization; is a disparaging, humiliating and contemptuous attitude or negative behavior towards an individual or an event. In alcohol dependence, individuals can be stigmatized for many reasons. This situation can affect the individual in many ways negatively. Stigmatized individuals benefit from treatment services at a lower probability, experience feelings of guilt and shame, and as a result of these emotions, self-esteem level of the individual reduces and academic and professional success is adversely affected. Besides, the social identity of the individual is affected and the quality of life decreases. For all these reasons, it is important to fight with stigmatization experienced by individuals who are alcohol dependent. In this context, stigmatizations that have been experienced through society, individuals themselves, family and health professionals by individuals who are addicted to alcohol have been put forward in this article and it is aimed to draw attention to this issue by considering nursing approach in the fight against stigmatization.
Keywords: Alcohol dependence; stigmatization; nursing